FAKTOR-FAKTOR DAN UPAYA DALAM MENANGANI STRESS PADA DOKTER DI TENGAH PANDEMI COVID 19 - Syahidah, Sumayyah Nurul (Mediapsi, 2022)
The Covid-19 pandemic that occurred in various parts of the world greatly impacted the work of physicians and other health workers. Active cases that continue to rise have resulted in physicians who are directly involved in treating patients at risk of experiencing stress at work. The stress that physicians feel is caused by many internal and external factors. The aim of this systematic review is to identify the causative factors and what efforts can be made to manage stress on the physicians in the midst of a pandemic. Systematic database searches using Springer Link, Scopus, Google Scholar, ScienceDirect, and Mendeley. Keywords to look for relevant research include: "Stress" and "Doctor" and "Covid-19"; "Stress" and "Health workers" and "Covid-19"; "Psychological" and "Covid-19" and "Doctor"; "Health workers" and "Covid-19" and “Psychologists”; “Covid-19” and “Stress” and “Physicians”; "Covid-19" and "Stress" and "Doctor"; "Covid-19" and "Impact" and "Stress" Pandemi Covid-19 yang terjadi di berbagai belahan dunia sangat berdampak pada kerja dokter dan tenaga kesehatan lainnya. Kasus aktif yang terus merangkak naik mengakibatkan para dokter yang terlibat langsung menangani pasien beresiko mengalami stress saat bekerja. Stress yang dirasakan diakibatkan oleh banyak faktor internal dan eksternal. Tujuan tinjauan sistematis adalah mengidentifikasi faktor-faktor penyebab dan usaha yang dapat dilakukan untuk menangani stress pada dokter di tengah pandemi. Pencarian data basis sistematis menggunakan Springer Link, Scopus, Google Scholar, ScienceDirect, dan Mendeley. Kata kunci untuk mencari penelitian yang relevan antara lain: “Stres” dan “Dokter” dan “Covid-19”; “Stres” dan “Tenaga kesehatan” dan “Covid-19”; “Psikologis” dan “Covid-19” dan “Dokter”; “Tenaga kesehatan” dan “Covid-19” dan Psikologis”; “Covid-19” dan “Stress” dan “Physicians”; “Covid-19” dan “Stress” dan “Doctor”;  “Covid-19” dan “Impact” dan “Stress”; “Covid-19” dan “Psychological” dan “Impact” dan “Doctor”; “Psychological” dan “Stress” dan “Doctor.”